Hydrogen isotopes in serial hair samples record season of death in a mummified child from 19th century San Francisco, CA. Issue 3 (5th September 2020) - Eerkens, Jelmer W.; Ryder, Alex; Evoy, Angela; Hull, Bryna
Abstract: Background: The mummified body of a small child was found in a sealed Barstow cast iron casket during construction activity in San Francisco in 2016. Using historical records and ancient DNA the child was determined to be Edith H. Cook. She was born 28 November, 1873 in the city of San Francisco, and died of "marasmus" on 13 October, 1876 also in San Francisco. Aims: Currently, there are few techniques for estimating human season of death in archaeological cases. Hydrogen isotope ratios (δ2H) in hair keratin is known to strongly correlate with drinking water. We explore δ2H in serial hair samples as a potential technique to estimate season of death by comparing the δ2H record from hair to the known date of death. Materials & Methods: Approximately 50 hairs were removed from the scalp, aligned from the root, and cut into 5cm serial sections, each representing approximately 2 weeks of growth, and the total sequence a total of 1 year of growth. δ2H was measured on each 5cm segment and compared to previously‐reported δ13C, δ15N, and δ34S values. Results: δ2H in the serial hair samples ranged between −56‰ and −48‰, consistent with her water values recorded in surface waters from San Francisco, and follow a sinusoidal pattern. Decreasing δ2H in terminal samples before death suggest Fall as the season of death, consistent with the known date of death. Discussion: This test case shows that archaeological hair preserves a seasonal signature in the form of changing keratin δ2H values that correlate to changing δ2H in surface drinking water. Terminal values in root record water ingested during the final week(s) before death. Conclusions: We argue that this technique can be used to estimate season of death in future archaeological or forensic cases where hair has been preserved but date of death is unknown. Abstract :